Performance Analysis of Co-firing Using Palm Kernel Shells in Chain Grate Stoker Coal Fired Power Plant 2 x 7 MW - Nainggolan, Irwan Firmanto; Hadiyanto, Hadiyanto; Utomo, Tony Suryo (Universitas Nahdlatul Ulama Blitar, 2023)
Co-firing is the efforts to reduce the use of fossil fuel (coal) form steam power plant. Adding biomass as a partial fuel to the boiler to reduce coal consumption thereby reducing carbon dioxide emissions which can have an impact on the greenhouse effect. This co-firing study implemented 5-20% palm kernel shells. The emission has decreased very significantly in the use of biomass by 20%, Carbon dioxide (CO2) from 7% to 0.9% and carbon monoxide (CO) from 759 Mg/Nm3 to 105 Mg/Nm3. Slagging index during is still within safe limits. Fouling index when coal firing and co-firings 5%, 15% and 20% are in the high category, while co-firing is 10% in the severe category. Base to acid ratio during co-firing test 5%, 10% and 15% in the high/severe category, while co-firing is 20% is still within safe limits. The potential for corrosion due to the presence of chlorine is Cl-induced active oxidation minor. The toxic properties samples obtained from various co-firings are still in safe condition and meet quality standards.